International trade - Neary, J. Peter (Aldershot, Hants, UK ; Brookfield, Vt., US : E. Elgar Pub. Co., 1995)
The author organised the collection by substantive real-world issues which different papers address. The papers are grouped into two volumes, with the division between them corresponding loosely to that between normative and positive questions. Volume l begins with a short section on the basic model of international exchange and then deals at length with issues of welfare and trade policy under a variety of assumptions about market structure. Volume ll begins with the central positive questions of production structure and trade patterns. It then turns to the literature on international investment, uncertainty, the real foundations of international macroeconomics and theories of technological progress and growth in open economies.
v. 1. Welfare and trade policy -- v. 2. Production structure, trade and growth.
Includes bibliographical references and indexes.
rpm 23/05/13
Loans
Keywords: International economic relations; Commercial policy; Competition, International; International trade